2020
DOI: 10.1038/s42003-020-1008-z
|View full text |Cite
|
Sign up to set email alerts
|

A negative feedback loop between JNK-associated leucine zipper protein and TGF-β1 regulates kidney fibrosis

Abstract: Renal fibrosis is controlled by profibrotic and antifibrotic forces. Exploring anti-fibrosis factors and mechanisms is an attractive strategy to prevent organ failure. Here we identified the JNK-associated leucine zipper protein (JLP) as a potential endogenous antifibrotic factor. JLP, predominantly expressed in renal tubular epithelial cells (TECs) in normal human or mouse kidneys, was downregulated in fibrotic kidneys. Jlp deficiency resulted in more severe renal fibrosis in unilateral ureteral obstruction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Our previous studies identified a novel anti-fibrotic molecule of JLP that is exclusively expressed in renal tubular epithelial cells (TECs) in kidney tissue, with the potential to antagonize the TGF-β1-elicited effects of ECM production, EMT, autophagy activation, apoptosis, and cycle arrest in TECs in kidney fibrosis progression. Inhibition of autophagy by gaining expression of Jlp in TECs significantly retarded the fibrotic lesions both in vitro and in vivo [18]. Together with the similar findings of the protective role of Jlp in peritoneal fibrosis reported in this study, we concluded that permanent and overactivation of autophagy, a result partly due to JLP loss, might promote the development of peritoneal fibrosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous studies identified a novel anti-fibrotic molecule of JLP that is exclusively expressed in renal tubular epithelial cells (TECs) in kidney tissue, with the potential to antagonize the TGF-β1-elicited effects of ECM production, EMT, autophagy activation, apoptosis, and cycle arrest in TECs in kidney fibrosis progression. Inhibition of autophagy by gaining expression of Jlp in TECs significantly retarded the fibrotic lesions both in vitro and in vivo [18]. Together with the similar findings of the protective role of Jlp in peritoneal fibrosis reported in this study, we concluded that permanent and overactivation of autophagy, a result partly due to JLP loss, might promote the development of peritoneal fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, it has also been found coordinating the cell process of autophagy [16]. Interestingly, our previous study demonstrated that JLP is involved in the regulation of TGF-β-induced renal fibrosis [17, 18], suggesting JLP as a potential anti-fibrosis factor. However, the role of JLP in peritoneal fibrosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tubulo-interstitial fibrosis, a hallmark of CKD, is a progressive process, which is driven by activation of interstitial myofibroblasts and by an increase in pro-fibrotic and pro-inflammatory signals. Thus TGF-β1 signaling, reactivation of developmental pathways, and a decrease in the expression of protective factors, such as Klotho and bone morphogenetic protein 7 (BMP7) are found [8,[48][49][50][51][52][53][54][55]. Klotho is an anti-aging protein, which is predominantly expressed in the kidney, where it functions as a coreceptor for FGF23, regulating phosphate and calcium reabsorption and calcitriol metabolism [56].…”
Section: Introductionmentioning
confidence: 99%
“…Paraffin-embedded sections with 4 μm thickness from each isolated kidney were stained with hematoxylin and eosin or Sirius red following the standard procedure, respectively. The tubular damage and tubulointerstitial fibrosis were measured as described [21] .…”
Section: Methodsmentioning
confidence: 99%